Prevalence of tuberculosis, COVID-19, chronic conditions and vulnerabilities among migrants and refugees: an electronic survey - Sonia Vivian de Jezus; Carolina Maia Martins Sales; Silvia das Dores Rissino; Helaine Jacinta Salvador Mocelin; Mariana Pereira da Silva Araújo; Ricardo Alexandre Arcêncio; Vania Maria Silva Araújo; Nahari de Faria Marcos Terena; Paula de Souza Silva Freitas; Ethel Leonor Noia Maciel (Universidade de São Paulo, 2023)
Abstract Objective: to analyze the prevalence of tuberculosis, coronavirus, chronic conditions and vulnerabilities among migrants and refugees in Brazil. Method: this is a cross-sectional study of the electronic survey type conducted with international migrants during the COVID-19 pandemic. Descriptive statistics was applied for the analysis, with calculation of position and dispersion measures. Regarding the categorical variables, relative and absolute frequencies were estimated. Results: the study participants were 553 migrants and refugees, verifying 3.07%, 7.2% and 27.3% prevalence of tuberculosis, COVID-19 and chronic conditions, respectively. Among the vulnerabilities, 32% reported unemployment, 37.6% moved to Brazil as a result of the social situation in their countries and 33.6% were living as refugees or sheltered people. Conclusion: tuberculosis, chronic diseases and COVID-19 presented higher prevalence values in migrants and refugees than in the general population. As this is a population group that still has significant difficulty accessing health services and social protection systems, based on diverse evidence, the study will subsidize public policies, Nursing care and the incorporation of new routines in the service.